Analisis Perubahan Luasan dan Kerapatan Tajuk Mangrove di Kecamatan Borong Kabupaten Manggarai Timur - Billah, Mu'tasim; Arthana, I Wayan; Restu, I Wayan; As-syakur, Abd. Rahman (Journal of Marine and Aquatic Sciences; Vol 6 No 1 (2020)DO - 10.24843/jmas.2020.v06.i01.p06, 2020)
The ecosystem of mangrove is one of unique and distinctive forms of forest ecosystem, has high economic and ecological value, but has highly vulnerable to damage if it’s unwise in management. The information about area of mangrove forest in East Manggarai District was too limited. Therefore it needs an analysis of area and density changes of mangrove headings in East Manggarai District. The objective of this research is analyzing area and density changes of mangrove headings in Borong Subdistrict of East Manggarai District. The techniques of this research past supervised classification , NDVI analysis and field observation. The data analysis are correlation and accuracy test. Based on the image analysis, the ecosystem area of mangrove in Borong Subdistrict of East Manggarai District from 2007 till 2017 decreased by 20,61 hectares from 90.99 to 70.38 hectares. Declining also occurred in density of mangrove headings level, where density level was reduces to medium or rare. Result of the accuracy test obtained overall accuracy value was 82%. The density of mangrove headings on rarely classification has NDVI value of less than 0.3272, the medium has 0.3272 to 0.413 and the dense has more than 0.413. Based on the correlation analysis the value of density and NDVI form a linear regression model y = 233.2x – 26.304, with a very strong correlation (r) is 0.93. The decreasing area and density of mangrove caused by human activity that are harmful the existence of mangrove forest.